Histone Deacetylases Exert Class-Specific Roles in Conditioning the Brain and Heart Against Acute Ischemic Injury - Aune, Sverre E.; Herr, Daniel J.; Kutz, Craig J.; Menick, Donald R. (Frontiers in Neurology, 2015)
Ischemia-reperfusion (IR) injury comprises a significant portion of morbidity and mortality from heart and brain diseases worldwide. This enduring clinical problem has inspired myriad reports in the scientific literature of experimental interventions seeking to elucidate the pathology of IR injury. Elective cardiac surgery presents perhaps the most viable scenario for protecting the heart and brain from IR injury, due to the opportunity to condition the organs prior to insult. The physiological parameters for the preconditioning of vital organs prior to insult through mechanical and pharmacologic maneuvers have been heavily examined. These investigations have revealed new insights into how preconditioning alters cellular responses to IR injury. However, the promise of preconditioning remains unfulfilled at the clinical level, and research seeking to implicate cell signals essential to this protection continues. Recent discoveries in molecular biology have revealed that gene expression can be controlled through posttranslational modifications, without altering the chemical structure of the genetic code. In this scenario, gene expression is repressed by enzymes that cause chromatin compaction through catalytic removal of acetyl moieties from lysine residues on histones. These enzymes, called histone deacetylases (HDACs), can be inhibited pharmacologically, leading to the de-repression of protective genes. The discovery that HDACs can also alter the function of non-histone proteins through posttranslational deacetylation has expanded the potential impact of HDAC inhibitors for the treatment of human disease. HDAC inhibitors have been applied in a very small number of experimental models of IR. However, the scientific literature contains an increasing number of reports demonstrating that HDACs converge on preconditioning signals in the cell. This review will describe the influence of HDACs on major preconditioning signaling pathways in the heart and brain.